Comparison of the Removal of Synthetic Wastewater Samples Containing Basic Blue 3 Dye Using Electrochemical and Adsorption Methods - Morali, Beyza; Budak, Turkan Borklu (MDPI, 2025)
Water pollution, a significant environmental issue, is growing more urgent. This study evaluated the effectiveness of adsorption and electrocoagulation methods in removing Ba-sic Blue 3 (BB3), a common dye used in the textile industry, from water. For the adsorption process, linden tree leaves-often used for health benefits in existing literature-were employed, while in the electrocoagulation (EC) method, an aluminum electrode was used. The results show that the optimal conditions for adsorption were an initial BB3 concentration of 5 mg/L, 50 mL of 0.9 g Tilia L. adsorbent, 60 min, 180 rpm, 30 degrees C, and pH 10, achieving a removal efficiency of 99.21%. The optimal conditions for electrocoagulation were 1 L of 15 mg/L initial BB3, a current density of 2.64 mA/cm2, 15 mL of 0.2 M KCl, a reaction time of 90 min, a stirring speed of 100 rpm, and a pH of 10, resulting in a removal efficiency of 97.98%. The results indicate that linden leaves, a natural and sustainable material, showed a slightly higher removal percentage (99.21%) in the EC method over a shorter period (60 min). Conversely, the EC method also achieved a significant removal rate (97.98%, 90 min). In summary, both methods demonstrate strong BB3 removal capabilities and could help improve wastewater treatment processes.
Keywords: basic blue 3; adsorption; linden leaves; Tilia L.; electrocoagulation (EC); AQUEOUS-SOLUTIONS; ELECTROCOAGULATION; Biochemistry & Molecular Biology; Chemistry